2021
DOI: 10.26434/chemrxiv-2021-zkz9w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site-Specific DNA Functionalization through the Tetrazene-Forming Reaction in Ionic Liquids

Abstract: Development of multiple chemical tools for deoxynucleic acid (DNA) labeling has facilitated wide use of their functionalized conjugates, but significant practical and methodological challenges remain to achievement of site-specific chemical modification of the biomacromolecule. As covalent labeling processes are more challenging in aqueous solution, use of nonaqueous, biomolecule-compatible solvents such as an ionic liquid consisting of a salt with organic molecule architecture, could be remarkably helpful in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…34 A new set of 15 N NMR data with 15 N isotopes on all the four possible nitrogen atoms of amine and azide groups disclosed that one of the peaks at ca. 300 ppm previously assigned to the N=N group of tetrazene was an artifact, 25 26 and introduction of only two 15 N isotopes out of the four possible nitrogens was observed. The formation of the urea group was confirmed through NMR, mass spectrometry, and infrared spectroscopy experiments.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…34 A new set of 15 N NMR data with 15 N isotopes on all the four possible nitrogen atoms of amine and azide groups disclosed that one of the peaks at ca. 300 ppm previously assigned to the N=N group of tetrazene was an artifact, 25 26 and introduction of only two 15 N isotopes out of the four possible nitrogens was observed. The formation of the urea group was confirmed through NMR, mass spectrometry, and infrared spectroscopy experiments.…”
mentioning
confidence: 80%
“…23 24 The initial set of our data including mass spectrometry and 1 H/ 15 N NMR studies suggested tetrazene as a potential reaction product (though one of the assigned peaks in 15 N NMR turned out to be an artifact in the later study). 25 26 Based on the set of data, we proposed a phosphazide-based coupling process without loss of N 2 gas as a potential reaction pathway (Scheme 2 C). 15 27 This initial hypothesis was supported by the report of similar electrophilic behavior of phosphazide intermediates for an intramolecular reaction between alkylated phosphazide and enolate species.…”
mentioning
confidence: 99%
See 2 more Smart Citations